A Comprehensive Analysis of Disruptive Technologies Effects on Several Businesses in the Post-COVID-19 Era (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The outbreak of Covid-19 has a significant impact on individuals and organizations. This paperoutlines the significance of Disruptive Technologies in overcoming the present challenges and be readyfor the “new normal”. It highlights the impact of digital innovation on various industries in Post Covid-19era. The technological seizure of power to enhanced the new possibilities and opportunities in allsegments of business. The study shows the relationship between the different business sectors andimplications of technological innovations. The focus is on stating the application and utility of these newtechnologies in generating the opportunities and new avenues in the post covid-19 era.The new norms are now adopted by the organizations to handle the challenges and threats generatedduring Covid-19I.e. Modern technology is developing more quickly than it did in the past in order to keepahead of the effects and develop new tools for creating a safer world. (Saxena et al., 2020). The newtechnologies are now supporting in achieving higher level of product and process quality. The need oftoday is to delight the customer with comfort and cost consciousness without compromising on quality,which is now possible to serve with the implementation of these technologies. Be it education orhealthcare, finance or sales and marking or labor market, the application of disruptive technologies hadleft no stones unturned.